Optical Fiber Sensing and Structural Health Monitoring Technology - Du, Yanliang; Sun, Baochen; Li, Jianzhi; Zhang, Wentao (Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on optical fiber sensing and structural health monitoring technologies. It provides detailed information on the basic theory of F-P optical fiber sensors, fiber Bragg grating sensors, fiber laser grating sensors and fully distributed optical fiber sensors. Drawing on the authors' research achievements and many years of practical experience in the field of engineering structure health monitoring, the book elaborates on the structural principle, design and manufacture of optical fiber sensors and monitoring technologies, and briefly describes advances made with regard to multiple engineering structures.